Insights into the tectonic evolution of the Svecofennian orogeny based on in situ Lu–Hf dating of garnet and apatite from Olkiluoto, southwestern Finland - Engström, Jon; Cutts, Kathryn; Glorie, Stijn; Heilimo, Esa; Jolis, Ester M.; Michallik, Radoslaw M. (Copernicus GmbH, 2025)
The southern Finland granites and associated migmatitic rocks have a complex metamorphic history, being affected by multiple events during the ca. 1.88-1.79 Ga Svecofennian orogeny. In this study, the prolonged tectonic evolution of migmatites and associated rocks in southwestern Finland has been investigated using the new in situ Lu-Hf method. Results reveal detailed temporal constraints for the tectonic evolution that can be linked to major events in adjacent tectonic blocks in both Finland and Sweden during the Svecofennian orogeny. The metamorphic peak at the Olkiluoto site occurred at 1829 +/- 19 Ma based on in situ Lu-Hf dating of garnet. The pressure-temperature (P-T) path for the rocks indicates a prograde evolution, with peak P-T conditions of 3-5 kbar and approximately 700 degrees C. Younger ages of ca. 1780 Ma obtained using both Lu-Hf and U-Pb systems in apatite inclusions in garnet indicate rapid cooling at 1780 Ma. Based on the metamorphic constraints and obtained ages, we link the Olkiluoto site to the H & auml;me orogenic belt in southern Finland and also support the proposed thermal-tectonic connection with the Ljusdal lithotectonic unit in central Sweden.